β-hydroxybutyrate impairs bovine oocyte maturation via pyruvate dehydrogenase (PDH) associated energy metabolism abnormality - Zhang, Kai-Yan; Guo, Jing; Zhan, Cheng-Lin; Yuan, Chong-Shan; Min, Chang-Guo; Li, Zhi-Qiang; Liu, Hong-Yu; Wang, Jun; Zhao, Jing; Lu, Wen-Fa; Ma, Xin (Frontiers in Pharmacology, 2023)
Ketosis is one of the most frequent and costly metabolic disorders in high-producing dairy cows, and negatively associated with the health and reproductive performance of bovine. Ketosis is mainly caused by the accumulation of ketone body β-hydroxybutyric acid and its diagnosis is based on βhydroxybutyrate (βHB) concentration in blood. In this study, we investigated the effects of βHB on bovine oocyte maturation in the concentration of subclinical (1.2mM) βHB and clinical (3.6mM). The results showed βHB disrupted bovine oocyte maturation and development capacity. Further analysis showed that βHB induced oxidative stress and mitochondrial dysfunction, as indicated by the increased level of reactive oxygen species (ROS), disrupted mitochondrial structure and distribution, and depolarized membrane potential. Furthermore, oxidative stress triggered early apoptosis, as shown by the enhanced levels of Caspase-3 and Annexin-V. Moreover, 3.6mM βHB induced the disruption of the pyruvate dehydrogenase (PDH) activity, showing with the decrease of the global acetylation modification and the increase of the abnormal spindle rate. Our study showed that βHB in 2 This is a provisional file, not the final typeset article subclinical/clinical concentration had toxic effects on mitochondrial function and PDH activity, which might affect energy metabolism and epigenetic modification of bovine oocytes and embryos.